UNDERSTANDING MAX WEBER'S THOUGHTS ON CAPITALISM IN INDONESIA - Aloysius Jondar; Donna Sampaleng; Fransana. P. Johannes de Fretes; Daniel Daniel (Bajang Institute, 2022)
Understanding Max Weber's thoughts on the life of capitalism in Indonesia is not an easy job because it requires in-depth observation in its implementation. Therefore, the problem in this study is what exactly is Max Weber's concept of the Protestant Ethic and the spirit of modern capitalism and is it still relevant to be actualized in Indonesia? The finding is that Max Weber's concept of Protestant ethics is the doctrine of predistination, asceticism, good manners, hard work, frugal living, use of time, money and wealth. The spirit of modern capitalism that is developing now is the rationalization of capitalism based on scientific principles and the development of personal wealth, production for the market, production for the masses. The relevance of Max Weber's thoughts about the spirit of capitalism applied in Indonesia is progressive because the spirit of capitalism is related to cultural values or human life. Max Weber's concept of Capitalism encourages the Indonesian people to take rationalization and innovation and be creative.